The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Handbuch Interdisziplinäre Geschlechterforschung 2017
DOI: 10.1007/978-3-658-12500-4_96-1
|View full text |Cite
|
Sign up to set email alerts
|

Sportsystem: Geschlechterforschung im Kontext von Sport und Bewegung

Abstract: Der Sport ist seit seiner Ausdifferenzierung als eigenständiges gesellschaftliches Teilsystem eine Männerdomäne und trägt u. a. durch institutionelle Arrangements, materielle Artefakte, Deutungsstrukturen und Interaktionsmechanismen zu einer Reproduktion von Geschlechterstereotypen und einer Naturalisierung von Geschlechterdifferenzen bei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This is evident on several levels: Women’s sports are less likely to be covered by the media compared to men’s sports, and female athletes are featured less often than male athletes. In addition, it was found that when women are reported on, it is often regarding their private lives and considered soft news, while men’s sports performance and abilities are the focus (Hartmann-Tews, 2019). This clearly shows that “the world of sports is a man’s world” (Hardin et al, 2008: 74) and that the underrepresentation of female sport journalists is a global phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…This is evident on several levels: Women’s sports are less likely to be covered by the media compared to men’s sports, and female athletes are featured less often than male athletes. In addition, it was found that when women are reported on, it is often regarding their private lives and considered soft news, while men’s sports performance and abilities are the focus (Hartmann-Tews, 2019). This clearly shows that “the world of sports is a man’s world” (Hardin et al, 2008: 74) and that the underrepresentation of female sport journalists is a global phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Previous sport science research has examined knowledge transfer, though mainly knowledge reuse, within specific projects or topics such as health (Rütten & Gelius, 2012), elite sport (Rütten, 2007), gender (Hartmann‐Tews & Dahmen, 2007), or sport medicine (Provvidenza & Johnston, 2009); within organizations such as sport governing bodies (O'Reilly & Knight, 2007) or professional team sport providers (Erhardt, Martin‐Rios, & Harkins, 2014); and at sport events (Parent, MacDonald, & Goulet, 2014). The reuse of scientific knowledge by various sport practitioners such as policymakers (Rütten & Gelius, 2012), employees of sport governing bodies (O'Reilly & Knight, 2007), athletes (Gerbing & Thiel, 2016), and coaches (Reade, Rodgers, & Spriggs, 2008b) represents a challenge already.…”
Section: Introductionmentioning
confidence: 99%